TATA KELOLA DAN FAKTOR LAIN YANG MEMPENGARUHI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - CINDY NATASHYA; ASTRID RUDYANTO (Media Bisnis, 2021)
This study aims to examine the effect of corporate governance (board size, board independence, women on board, internationalization) and other firm characteristics (firm size, profitability, financial leverage, and listing age) on corporate social responsibility disclosure. This research used 132 manufacturing companies listed in Indonesia Stock Exchange during years 2015-2018. Samples were selected by purposive sampling method. Data analysis was performed with SPSS 19th Version Program. Multiple regression was used to analyze data. The result shows that board size, firm size, profitability, and listing age have influence on corporate social responsibility disclosure. While board independence, women on board, financial leverage, and internationalization have no effect on corporate social responsibility disclosure.